2007
DOI: 10.1002/art.22483
|View full text |Cite
|
Sign up to set email alerts
|

Cell markers, cytokines, and immune parameters in cement mason apprentices

Abstract: Objective. Cement masons are known to have significant silica exposure, and silica exposure and silicosis are thought to increase risk of autoimmune disease. Because the mechanisms remain obscure, with inconclusive reports of systemic immune effects following silica exposure, our goal was to identify potential early markers of silica-related immunologic and respiratory effects. Methods. We conducted a cross-sectional study of cement mason apprentices and electrician (control) apprentices. Demographics, dust ex… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

3
16
1

Year Published

2010
2010
2021
2021

Publication Types

Select...
6
2

Relationship

0
8

Authors

Journals

citations
Cited by 28 publications
(20 citation statements)
references
References 26 publications
3
16
1
Order By: Relevance
“…Recent studies have demonstrated that silicosis is an immune-associated disease as pulmonary silicosis is usually accompanied by abnormalities of immune parameters, and the patients with silicosis have a tendency to suffer from autoimmune diseases (Valletta et al, 1992;Cooper et al, 2002;Carlsten et al, 2007;Sauni et al, 2012). In this study, we found that IgG levels were elevated in patients with silicosis, and that this elevation could be downregulated by MSC therapy.…”
Section: Discussionsupporting
confidence: 50%
“…Recent studies have demonstrated that silicosis is an immune-associated disease as pulmonary silicosis is usually accompanied by abnormalities of immune parameters, and the patients with silicosis have a tendency to suffer from autoimmune diseases (Valletta et al, 1992;Cooper et al, 2002;Carlsten et al, 2007;Sauni et al, 2012). In this study, we found that IgG levels were elevated in patients with silicosis, and that this elevation could be downregulated by MSC therapy.…”
Section: Discussionsupporting
confidence: 50%
“…In addition, occupational exposure to silica, the major component of cement, may increase the risk of autoimmune disease. Carlsten et al, (2007) recently showed that cement masons had higher levels of proinflammatory cytokines and lower percentages of CD25+ and CD69+ lymphocytes compared to control. This led them to suggest that cement masons may be at a greater risk of a systemic proinflammatory state which could be linked to immune dysregulation (Carlsten et al, 2007).…”
Section: Discussionmentioning
confidence: 99%
“…Carlsten et al, (2007) recently showed that cement masons had higher levels of proinflammatory cytokines and lower percentages of CD25+ and CD69+ lymphocytes compared to control. This led them to suggest that cement masons may be at a greater risk of a systemic proinflammatory state which could be linked to immune dysregulation (Carlsten et al, 2007). It is conceivable that such a proinflammatory state and the accompanying autoimmune disease process may occur in the haemopoietic system thereby accounting for the results of the present study.…”
Section: Discussionmentioning
confidence: 99%
“…The inflammatory effects of silica in the peripheral lung, which may eventually lead to the development of silicosis, might be seen as increased levels of alveolar NO. The effect of silica exposure on exhaled NO has been reported in only one previous study, which found no effect 11. However, the study measured exhaled NO at a single exhalation flow rate, using an off-line method, which is not sensitive to increased alveolar NO concentrations.…”
Section: Introductionmentioning
confidence: 88%